Key Residues in Octyl‐Tridecaptin A1 Analogues Linked to Stable Secondary Structures in the Membrane. Issue 9 (9th May 2014) - Cochrane, Stephen A.; Findlay, Brandon; Vederas, John C.; Ratemi, Elaref S.
Abstract Tridecaptin A1 is a linear antimicrobial lipopeptide comprised of 13 amino acids, including three diaminobutyric acid (Dab) residues. It displays potent activity against Gram‐negative bacteria, including multidrug‐resistant strains. Using solid‐phase peptide synthesis, we performed an alanine scan of a fully active analogue, octyl‐tridecaptin A1, to determine key residues responsible for activity. The synthetic analogues were tested against ten organisms, both Gram‐positive and Gram‐negative bacteria. Modification of D‐Dab8 abolished activity, and marked decreases were observed with substitution of D‐allo‐Ile12 and D‐Trp5. Circular dichroism showed that octyl‐tridecaptin A1 adopts a secondary structure in the presence of model phospholipid membranes, which was weakened by D‐Dab8‐D‐Ala, D‐allo‐Ile12‐D‐Ala, and D‐Trp5‐D‐Ala substitutions. The antimicrobial activity of the analogues is directly correlated to their ability to adopt a stable secondary structure in a membrane environment.